Comparative study between luenberger observer and extended kalman filter for fault-tolerant control of induction motor drives - T. Roubache; S. Chaouch; MS. Nait-Said (International Information and Engineering Technology Association, 2018)
In this paper, a robust active fault tolerant control (AFTC) scheme is proposed for induction motor drives (IMD) via input-output linearization control (IOLC) and nonlinear observer. In order to estimate the states and to reconstruct the faults, two different observers are used; a Luenberger observer (LO) and an extended kalman filter (EKF). Further we introduce feedback linearization strategy by choosing the output function as the rotor speed and flux square. To provide a direct comparison between these FTCs schemes, the performance is evaluated using the control of IMD under failures, variable speed, and variable parameters, finally the obtained results show that the proposed controller with the proposed observers provides a good trajectory tracking, and these schemes are robust with respect to faults, parameter variations, and external load disturbances for induction motor drive system.